Zoonosis emergence linked to agricultural intensification and environmental change - Jones, B.A.; Grace, Delia; Kock, R.; Alonso, Silvia; Rushton, Jonathan; Said, Mohammed Yahya; McKeever, Declan J.; Mutua, Florence K.; Young, J.; McDermott, John J.; Pfeiffer, Dirk U. (National Academy of Sciences, 2013)
A systematic review was conducted by a multidisciplinary team to analyze qualitatively best available scientific evidence on the effect of agricultural intensification and environmental changes on the risk of zoonoses for which there are epidemiological interactions between wildlife and livestock. The study found several examples in which agricultural intensification and/or environmental change were associated with an increased risk of zoonotic disease emergence, driven by the impact of an expanding human population and changing human behavior on the environment. We conclude that the rate of future zoonotic disease emergence or reemergence will be closely linked to the evolution of the agriculture–environment nexus. However, available research inadequately addresses the complexity and interrelatedness of environmental, biological, economic, and social dimensions of zoonotic pathogen emergence, which significantly limits our ability to predict, prevent, and respond to zoonotic disease emergence.